Spatial Variation in Thermal Behaviour and its Correlation with Bio-Physical Features in Varanasi City - Kushawaha, Shailendra; Sharma, V.N. (National Geographical Journal of India, 2022)
The rapid urbanization has changed the landscape of cities by increasing the built-up area and their density. This haphazard development of houses and other types of gray infrastructure replaced vegetation cover and water bodies. This built-up infrastructure has changed the microclimate of cities by increasing temperature to its surroundings. This paper analys its spatial variation in land surface temperature and its correlation with vegetation cover, built-up area and water bodies through Normalized Difference Vegetation Index (NDVI), Normalized Difference Built-up Index (NDBI) and Modified Normalized Difference Water Index (MNDWI). This analysis shows negative non-linear strong correlation (R2 = 0.9621) with vegetation cover, that means vegetation cover controls the surface temperature of urban area by the flux of evapotranspiration. Positive linear strong correlation (R2 = 0.8417) with built-up surface reveals that it strengthens the surface temperature of city by trapping shortwave solar radiation while negative linear strong correlation ((R2 =1.00) with water bodies shows that waterbodies maintain the temperature of their surroundings by the flux energy of vaporization. NDVI, NDBI and MNDWI Green, Red, Infrared and Shortwave Infrared band of Landsat 8 satellite images have been used for analysis and LST has been calculated by using Band 10 and Band 11 of TIRS/OLI sensor of LANDSAT 8 satellite image. The correlations reveal that improving the condition of biophysical features can manage the temperature of the city